Sosiaal-wetenskaplike kritiese eksegese van Nuwe-Testamentiese tekste – "n voortgaande debat sonder einde - Aarde, Andries van (HTS teologiese studies, 2007)
Social-scientific critical exegesis of New Testament texts – an ongoing debate without end The aim of this article is to describe the multifarious facets of social-scientific critical exegesis. It consists of a discussion of the theoretical epistemological premises behind anthropological models employed in the exegesis of Biblical tests. The article focuses in the second instance on work published by members of the Context Group. It subsequently discusses the socio-rhetorical approach and ideology criticism. The article concludes with the contribution made by hermeneutics of suspicion and cultural criticism. The article forms the third in a series of three that aims to introduce social-scientific critical exegesis of New Testament texts. The first article was of an introductory nature, the second explains some models and methods and the third discusses the critique against the approach as if it reflects positivism and concludes with an emphasis on cultural criticism as a hermeneutical challenge.